Characterisation of lead barium zirconate thin films for utilisation of the electrocaloric effect - Shaw, Christopher P.; Zhang, Qi; Correia, T. M.; Weaver, P. M. (Elsevier, 2016)
Characterisation of a composition of Lead Barium Zirconate thin films deposited by a spin coating sol-gel process onto platinised silicon substrates has been undertaken to investigate a potential application utilising the reported electrocaloric properties of the material. Xray diffraction studies revealed that above 700 °C the presence of pyrochlore phase was replaced by ferroelectric phase but the identification of antiferroelectric phases previously reported could not be identified. Wet etching of the films produced an insoluble residue containing only evidence of zirconium out of the original three metals, which resembled a skeletal structure similar to the original rosette morphology of the annealed films. Elemental analysis of the annealed films using EDX indicated a non-target Pb:Ba:Zr ratio, which suggested a reduced Zr content of the films. “Solution-like” rather than “sol-like” nature of the spin coated sol and phase boundary proximity are proposed for reported observations, and a mechanism is proposed to account for the unusual observed trend in dielectric constant.